(3GdcGed (B- (3aj GdCOHs - (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, GdeHQO , CHh GdYHGS,J (B286 (3g` s
(3ChdgG (B:s
(3HGH ef CNHGQ GdNhGQL bGd CHhGdYHGS(B: (3PcQ Cgd GdYde ef GdoUaQjI Cf GdNhGQL dqeG YRehG Ydi GdHjYI s
(3BNQgG (B:s
(3aGdhba jNQLhf GdQShd hEjGce Cj hjNQLhfce dCf JDefhG HGddg QHce s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3HChdgG bQGAI SfI(B421(3g`s
(3fSNI KGdKIs
(3hYdi ghGeTgG JYdjbGJ hJUMjMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
Keywords: (3GdCOHs